2019
DOI: 10.1016/j.taap.2019.04.025
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of Hemin and Sestrin2 modulates oxidative stress and colon tumor growth

Abstract: Several large epidemiological and animal studies demonstrate a direct correlation between dietary heme iron intake and/or systemic iron levels and cancer risk in several cancers including colorectal cancer (CRC). However, the precise mechanisms for how heme iron contributes to CRC and how cancer cells respond to heme iron-induced stress are still unclear. Previously we have shown that one of the stress-inducible proteins, Sestrin2 (SESN2), is a novel tumor suppressor in colon by limiting endoplasmic reticulum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 72 publications
2
21
0
Order By: Relevance
“…Similarly, treatment of the hepatic cell line HH4 with ferric ammonium citrate resulted in signifcantly increased ROS levels only at concentrations above 1000 µM, while incubation of cells with 100 µM ferric ammonium citrate or ferric chloride did not augment basal ROS levels 31,32 . In support of our results, another study also reported ROS generation in HCT116 and RKO cells treated with 100 µM hemin 33 . Furthermore, we showed that hemin, in contrast to inorganic iron, caused DNA strand breaks as well as oxidative DNA damage (i.e., 8-oxoG) in HCEC and CRC cells.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, treatment of the hepatic cell line HH4 with ferric ammonium citrate resulted in signifcantly increased ROS levels only at concentrations above 1000 µM, while incubation of cells with 100 µM ferric ammonium citrate or ferric chloride did not augment basal ROS levels 31,32 . In support of our results, another study also reported ROS generation in HCT116 and RKO cells treated with 100 µM hemin 33 . Furthermore, we showed that hemin, in contrast to inorganic iron, caused DNA strand breaks as well as oxidative DNA damage (i.e., 8-oxoG) in HCEC and CRC cells.…”
Section: Discussionsupporting
confidence: 91%
“…The gene expression of Sesn2 upregulated by miR182-5p suppression in arsenic treatment functions as an antioxidant in Uppsala 87 malignant glioma (U87MG), human lung adenocarcinoma H1299, and A549 cell lines (Lin et al, 2018). Sesn2 would promote colorectal cancer cell growth in the iron-rich environment by suppressing ROS (Kim et al, 2019). Sestrins promote anchorage-independent (anoikis resistance) growth of human endometrial cancer cells (Kozak et al, 2019).…”
Section: Sestrins In Nutrient Stress-sensing and Metabolic Dysfunctionmentioning
confidence: 99%
“…Our data thus suggest that these correlations between SESN2 and cell cycle-associated genes are independent of the role of CDKN1A and CDKN1B as tumor suppressors in the tumor of patients with endometrial cancer. SESN2 suppresses migration and proliferation in vitro, and tumor growth in vivo in colorectal cancer [27,[55][56][57]. However, the relationship between growth and SESN2 expression has remained unanswered in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SESN2 suppresses migration and proliferation in vitro, and tumor growth in vivo in colorectal cancer [ 27 , 55 , 56 , 57 ]. However, the relationship between growth and SESN2 expression has remained unanswered in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%